2018
DOI: 10.3390/ijms19061753
|View full text |Cite
|
Sign up to set email alerts
|

The Late Stages of Melanogenesis: Exploring the Chemical Facets and the Application Opportunities

Abstract: In the last decade, the late stages of melanin biosynthesis involving the oxidative polymerization of 5,6-dihydroxyindole (DHI) and 5,6-dihydroxyindole-2-carboxylic acid (DHICA) have been extensively investigated. Most of the information derived from a biomimetic approach in which the oxidation of melanogenic indoles was carried out under conditions mimicking those occurring in the biological environment. Characterization of the early oligomers allowed for drawing a structural picture of DHI and DHICA melanins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 90 publications
0
58
0
1
Order By: Relevance
“…Tyrosinase related protein 1 (TRP-1) is believed to catalyze the oxidation of DHICA to melanin. Although all the three enzymes, tyrosinase, TRP-1, and TRP-2 are involved in the melanogenesis pathway, tyrosinase is exclusively necessary for melanogenesis [11,[23][24][25][26][27][28][29][30].…”
Section: Tyrosinase and Its Key Role In Melanin Synthesismentioning
confidence: 99%
“…Tyrosinase related protein 1 (TRP-1) is believed to catalyze the oxidation of DHICA to melanin. Although all the three enzymes, tyrosinase, TRP-1, and TRP-2 are involved in the melanogenesis pathway, tyrosinase is exclusively necessary for melanogenesis [11,[23][24][25][26][27][28][29][30].…”
Section: Tyrosinase and Its Key Role In Melanin Synthesismentioning
confidence: 99%
“…In addition to the enzymatic activity, TRP1 is also a stabilizing protein for tyrosinase, as its role is still unclear depending on the metal cofactor found at the active site [14,15]. DHI as well DHICA can be oxidized in the absence of any enzyme to their respective o-quinones by oxygen and ROS generated during previous reactions [16]. In any case, eumelanin is basically a polymer with mixture of decarboxylated (DHI) and carboxylated (DHICA) 5,6-oxygenated indole units at different oxidation degrees (5,6-dihydroxy, semiquinone and 5,6-quinone units).…”
Section: Natural Skin Pigments For Photoprotection: Melanin and Melanmentioning
confidence: 99%
“…Alternatively, in the last years, other melanin-related compounds have been proposed to increase the absorption and general properties of natural melanin in order to be used in cosmeceutics. In this regard, in exploring the maintenance role of the carboxyl group in polymers, studies revealed that the use of DHICA methyl ester improves the antioxidant and protective effects of the final polymer, particularly by the higher absorption of UVA light [16,44].…”
Section: Natural Compounds Related To Animal Melaninmentioning
confidence: 99%
“…Melanins are the primary determinants of skin, hair and exoskeletal pigmentation in mammals, birds and insects [1][2][3][4][5][6], and their importance has been growing over the past few years not only from a biological point of view, related to their role in the human body, but also for the exploitation of their unique properties in biomedicine or in the cosmetic and health sectors [7][8][9][10][11][12][13][14][15][16]. These pigments are biosynthesized in melanocytes, starting with the oxidation of tyrosine to dopaquinone catalyzed by the enzyme tyrosinase ( Figure 1) [1,17,18].…”
Section: Introductionmentioning
confidence: 99%